2012
DOI: 10.1021/jm3012239
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective Pyrazolopyrimidine Janus Kinase 2 Inhibitors

Abstract: The discovery of somatic Jak2 mutations in patients with chronic myeloproliferative neoplasms has led to significant interest in discovering selective Jak2 inhibitors for use in treating these disorders. A high-throughput screening effort identified the pyrazolo[1,5-a]pyrimidine scaffold as a potent inhibitor of Jak2. Optimization of lead compounds 7a-b and 8 in this chemical series for activity against Jak2, selectivity against other Jak family kinases, and good in vivo pharmacokinetic properties led to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…Furthermore, no systematic study including reaction optimization and exploration of the substrate scope has been disclosed. [34] Poorly explored cross-coupling methodologies in this field and the potential bioactivity of the target arylated aminopyrazoles encouraged us to further explore the arylation of aminopyrazole derivatives at the 4-position. Herein, we present our results of the Pd-catalyzed C-C cross-coupling reactions of pyrazoles with a range of aryl-, heteroaryl-, and styrylboronic acids or esters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no systematic study including reaction optimization and exploration of the substrate scope has been disclosed. [34] Poorly explored cross-coupling methodologies in this field and the potential bioactivity of the target arylated aminopyrazoles encouraged us to further explore the arylation of aminopyrazole derivatives at the 4-position. Herein, we present our results of the Pd-catalyzed C-C cross-coupling reactions of pyrazoles with a range of aryl-, heteroaryl-, and styrylboronic acids or esters.…”
Section: Introductionmentioning
confidence: 99%
“…The high resolution (2.30 Å) crystal structure of human JAK2 in complex with an inhibitor, N-[1-(3-chlorophenyl)-3-methyl-1H-pyrazol-5-yl] pyrazolo [1,5-a] pyrimidine-3-carboxamide, was downloaded from the RCSB Protein Data Bank (PDB code: 4HGE) (17). For protein preparation, the active site for docking was identified from the binding site of the inhibitor in the co-crystal structure.…”
Section: Methodsmentioning
confidence: 99%
“…A series of pyrazolopyrimidine compounds was reported by Genetech as being potent JAK2 inhibitors with moderate to good selectivity [39]. The X-ray structure of an earlier lead compound, 27, bound to JAK2 showed several key interactions that led to more potent compounds.…”
Section: Key Termmentioning
confidence: 99%
“…S*BIO (Singapore) described a series of macrocyclic aminopyrimidines as being selective JAK2/TYK2/FLT3 inhibitors [49][50][51][52]. Through extensive modeling studies, pacritinib (SB1518, 38) and SB1578 (39) were shown to bind to the hinge of the kinase via their aminopyrimidine moieties [53]. They both make a further hydrogen bond to the kinase from their benzylic oxygens to Ser-936.…”
Section: Key Termmentioning
confidence: 99%